2019
DOI: 10.24059/olj.v13i2.1665
|View full text |Cite
|
Sign up to set email alerts
|

From Posts to Patterns: A Metric to Characterize Discussion Board Activity in Online Courses

Abstract: Asynchronous text based discussion boards are included in many online courses, however strategies to compare their use within and between courses, from a disciplinary standpoint, have not been well documented in the literature. The goal of this project was to develop a multi-factor metric which could be used to characterize discussion board use in a large data set (n=11,596 message posts) and to apply this metric to all Mathematics courses offered in the January 2008 term by the Center for Distance Learning at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 38 publications
2
32
0
1
Order By: Relevance
“…According to Balakrishnan (2011), CSCL provides students and instructors the flexibility to discuss contents in depth and build knowledge from a distance in an online collaborative learning environment (Shukor, Tasir, Van der Meijden, & Harun, 2014). According to Bliss and Lawrence (2009), cultural awareness in online classrooms helps to increase intercultural knowledge, understanding, and respect among students in the classroom. This shows that the use of best practices and online activities in an online course helped instructors and students share ideas and discuss issues, which allowed students to become active participants and make meaningful contributions to the learning contents or concepts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Balakrishnan (2011), CSCL provides students and instructors the flexibility to discuss contents in depth and build knowledge from a distance in an online collaborative learning environment (Shukor, Tasir, Van der Meijden, & Harun, 2014). According to Bliss and Lawrence (2009), cultural awareness in online classrooms helps to increase intercultural knowledge, understanding, and respect among students in the classroom. This shows that the use of best practices and online activities in an online course helped instructors and students share ideas and discuss issues, which allowed students to become active participants and make meaningful contributions to the learning contents or concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other studies (Bliss & Lawrence, 2009;Dawson, 2006) found that online collaboration tools have the potential to promote learners' sense of community, increase the knowledge flow between students and facilitate their participation in online environments (Hrastinski, 2006). Research has revealed that many students prefer to work with peers from their own cultural backgrounds (Moore & Hampton, 2015;Rienties et al, 2013).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…This is adapted from the term educationally valuable talk (EVT). EVT is defined as a particular interaction pattern in online discussion threads characterized as dialogic exchanges whereby a participant collaboratively displays construction, and at times, critical engagement with the ideas or key concepts that make up the topic of an online discussion, and builds knowledge through reasoning, articulations, creativity, and reflection (Bliss & Lawrence, 2009). A more useful distinction of “quality” can be made by determining whether a post is educationally valuable or educationally less valuable.…”
Section: Resultsmentioning
confidence: 99%
“…Other research (Balaji & Chakrabarti, 2010;Bassett, 2011;Du, Zhang, Olinzock, & Adams, 2008;Shana, 2009;Zhang, Goa, Ring, & Zhang, 2007) has examined and explored how students' communication skills, critical thinking skills, and literacy skills and their academic achievements improve overall through ODBs. Some research (Bliss & Lawrence, 2009;Peterson-Karlan, 2011;Kessler, Bikowski, & Boggs, 2012;Lin & Yang, 2011;Ritchie & Black, 2012;Wegmann & McCauley, 2014) has focused on discovering the importance of integrating discussion boards, online chats, and Wikis into the education process. In addition, they explored how students improve in their writing skills by using Web-based boards in English writing courses, and some in many-to-many/group-to-group collaborative writing.…”
Section: Literature Reviewmentioning
confidence: 99%